2021
DOI: 10.1186/s41021-021-00173-7
|View full text |Cite|
|
Sign up to set email alerts
|

Species diversity and molecular analysis of opportunistic Mycobacterium, Nocardia and Rhodococcus isolated from the hospital environment in a developing country, a potential resources for nosocomial infection

Abstract: Background Hospital environmental resources have a significant role in cross-transmission of opportunistic pathogens such as actinomycetes species to the patients. Actinomycetes have a remarkable capability to survive in adverse and harsh conditions of hospital environments; therefore, they are a threat to the health of patients. Due to this issue, we aimed to determine the frequency and diversity of actinomycetes species in hospital soil, water and dust by using a combination of conventional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Nosocomial infections like pneumonia, urinary tract infections, brain abscesses, catheter‐related bloodstream infections, and bacteremia in hospitals are caused by microorganisms like E. coli , S. aureus , C. albicans , N. abcessus , and N. cyriacigeorgica . [ 17,18 ] Nosocomial infections have had economic and clinical impacts on the healthcare system. [ 30 ] Hence, discovering novel antimicrobial drugs has become popular among researchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nosocomial infections like pneumonia, urinary tract infections, brain abscesses, catheter‐related bloodstream infections, and bacteremia in hospitals are caused by microorganisms like E. coli , S. aureus , C. albicans , N. abcessus , and N. cyriacigeorgica . [ 17,18 ] Nosocomial infections have had economic and clinical impacts on the healthcare system. [ 30 ] Hence, discovering novel antimicrobial drugs has become popular among researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Infections, especially nosocomial ones, continue to cause significant problems in hospitals worldwide. [ 17,18 ] Cases caused by pathogenic microorganisms are regularly reported by medical doctors and researchers. For example, Chmielarczyk et al reported that M. luteus , S. aureus , E. facealis , Salmonella spp, E. coli , and C. albicans were isolated from bloodstream infections more than ten times between 2016 and 2019 in their 4‐year laboratory‐based study in the south of Poland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human patients M. setense was rarely isolated in different countries, e.g., in Asia [ 12 , 13 ] and France [ 5 , 14 ]. In the environment, this NTM species was found in Iran in various samples from hospitals, e.g., a water system [ 15 , 16 ], soil and dust [ 17 ] and the environment [ 18 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The proportion of patients without immunodeficiency accounts for no more than 10-15% of cases (Kamboj et al, 2005;Yamshchikov et al, 2010). The ubiquitous distribution of representatives of the genus Actinomyces poses a serious threat to the treatment of the diseases they cause (Siavashifar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%